INVESTIGATING THE LINK BETWEEN KNOWLEDGE SHARING AND INNOVATION CAPABILITY (Journal of Technology and Operations Management, 2016)
Nowadays, knowledge sharing has been acknowledged as a fundamental concept to achieve competitiveness. Organizations are encouraged to promote knowledge sharing since this activity will improve an organization’s competitive advantage through innovation capability. The purpose of this paper is to investigate the roles of knowledge sharing, individual factor, and innovation capability. Mainly, individual is a critical factor that influences whether employees wish to conduct knowledge sharing practice or not. To cope with barriers in knowledge sharing practice, organization must create a supportive culture. This paper suggested that organizations need to develop knowledge sharing culture as it is a key driver for the success of knowledge sharing to stimulate innovation capability.